The European internist – a promising prospect or an illusion? - Tjen, H. S. L. M. (Eesti Arst, 2003)
Contemporary internal medicine evolved from “innere Medizin” in Germany and Austria in the early 1880’s and it describes a discipline covering the specific scientific knowledge of organ pathophysiology. The primary mission of early internists was diagnosis and they were called in as consultants for the most difficult diagnostic cases.